Beyond Physical Barriers: The Perception of Accessibility as the Main Driver of User Satisfaction in the Valparaíso Railway System - Muñoz-Canales, C (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
This study examines the influence of perceived inclusion and accessibility dimensions on user satisfaction within the Valparaíso Metro system in Chile. The research focuses on a quantitative survey conducted with 192 regular passengers along the Limache–Puerto corridor of the EFE Valparaíso railway network. A structured questionnaire comprising 58 Likert-scale items assessed perceived accessibility, inclusion, intermodality, safety, environmental effectiveness, and overall satisfaction. Data were analyzed using Confirmatory Factor Analysis (CFA) with the WLSMV estimator based on polychoric correlations, followed by multiple linear regression with robust standard errors. Results show that the proposed model explains 72% of the variance in overall satisfaction (Adjusted R2 = 0.71). Among the five predictors, perceived inclusion emerged as the most influential factor (β = 0.64, p < 0.001), surpassing perceived accessibility (β = 0.18, p < 0.01) and intermodality (β = 0.11, p < 0.05). Safety and environmental conditions showed weaker but significant associations. These findings provide empirical evidence that inclusive perceptions—rather than merely physical or operational aspects—constitute the primary driver of satisfaction in urban railway systems. The study contributes to accessibility research by integrating psychosocial and perceptual dimensions into the evaluation of public transport performance. It also offers actionable implications for inclusive design, passenger communication, and service management strategies in metropolitan rail systems, particularly in Latin American contexts undergoing infrastructure expansion and modernization. © 2025 by the authors.